A fixed point operator for a nonlinear boundary value problem - Amster, P. (2002)
We study a semilinear second order equation with a nonlinear boundary condition for the axial deformation of a nonlinear elastic beam in the presence of friction. Under appropriate conditions we define a fixed point operator in order to obtain solutions for this equation. ©c 2002 Elsevier Science.